The Rise of Euroscepticism in Three Acts : A Comparative Perspective of Anti-EU Attitudes in Central Europe - Hošková, Kateřina; Bič, Josef; Števík, Eva Isabelle; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
Although Euroscepticism, a term unifying negative attitudes towards the European Union (EU), has been a phenomenon of European politics and society since the 1980’s, a series of three European crises starting in 2009 created an unprecedentedly high level of mistrust in the European Union. The thesis focuses on the effect of the Eurozone crisis of 2009, European migrant crisis which started in 2015, and the United Kingdom’s intention to withdraw from the European Union in 2016. The aim is to analyse, using the utilitarian and European identity methods, the impact of the three crises on the level of Euroscepticism among citizens of three Central European Member States (Czech Republic, Poland, Slovakia) and France. The countries were chosen as representatives of perceived EU scepticism and positivism.
Vedoucí práce: Josef Bič
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses